2002
DOI: 10.1029/2001wr001123
|View full text |Cite
|
Sign up to set email alerts
|

Transport and retention of coarse woody debris in mountain streams: An in situ field experiment of log transport and a field survey of coarse woody debris distribution

Abstract: [1] Although coarse woody debris (CWD) is an important component of stream ecosystems in forested areas, the processes of CWD distribution, transport, and retention have not been clarified. In this study the distribution process of CWD pieces shorter than the bankfull width (S-CWD) is discussed using an in situ field experiment of log transport and a field survey of CWD distribution in mountain streams. The transport experiment showed that transport distance has a close relation to flow depth and also implied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 20 publications
2
107
1
Order By: Relevance
“…As for the length ratio, the draft ratio may affect the probability that a piece is halted (by friction with the stream bed in this case) before it can escape a 10 m section. Although prior research [Braudrick and Grant, 2001;Haga et al, 2002] suggests that draft ratio may be important to entrapment, our analysis found that draft ratio plays a relatively minor role in mobilization.…”
Section: Controls Of Mobilizationcontrasting
confidence: 86%
See 1 more Smart Citation
“…As for the length ratio, the draft ratio may affect the probability that a piece is halted (by friction with the stream bed in this case) before it can escape a 10 m section. Although prior research [Braudrick and Grant, 2001;Haga et al, 2002] suggests that draft ratio may be important to entrapment, our analysis found that draft ratio plays a relatively minor role in mobilization.…”
Section: Controls Of Mobilizationcontrasting
confidence: 86%
“…[7] Another study attempted to combine the detailed hydraulic predictions of flume studies with the realism of a field study and determined that mobilization was influenced by the ratio of piece diameter to water depth [Haga et al, 2002]. However, that study had two major limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the shape of the woody debris pieces being cylindrical, and neglecting the influence of buoyancy, the hydrodynamic force can be expressed as follows (Haga et al 2002):…”
Section: Woody Materials Entrainment and Transportmentioning
confidence: 99%
“…4, the dynamics of a single woody material element with known dimensions can be described within a simplified scheme as follows (Haga et al 2002):…”
Section: Woody Materials Entrainment and Transportmentioning
confidence: 99%
See 1 more Smart Citation